2018
DOI: 10.15252/embr.201845964
|View full text |Cite
|
Sign up to set email alerts
|

Notch‐inducing hydrogels reveal a perivascular switch of mesenchymal stem cell fate

Abstract: The fate of mesenchymal stem cells (MSCs) in the perivascular niche, as well as factors controlling their fate, is poorly understood. Here, we study MSCs in the perivascular microenvironment of endothelial capillaries by modifying a synthetic 3D biomimetic poly(ethylene glycol) (PEG)-hydrogel system We show that MSCs together with endothelial cells form micro-capillary networks specifically in soft PEG hydrogels. Transcriptome analysis of human MSCs isolated from engineered capillaries shows a prominent switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 72 publications
(117 reference statements)
3
45
0
Order By: Relevance
“…These findings are also consistent with other studies noting that increasing crosslink degradability or a more loosely crosslinked network structure correlate with increased capillary morphogenesis. Furthermore, in adipocyte‐derived stem cell‐EC cocultures, others have observed evidence that plasmin‐mediated ECM degradation becomes increasingly important in densely crosslinked fibrin .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are also consistent with other studies noting that increasing crosslink degradability or a more loosely crosslinked network structure correlate with increased capillary morphogenesis. Furthermore, in adipocyte‐derived stem cell‐EC cocultures, others have observed evidence that plasmin‐mediated ECM degradation becomes increasingly important in densely crosslinked fibrin .…”
Section: Discussionsupporting
confidence: 93%
“…Our model also provides a tool to investigate matrix remodeling in organotypic capillary morphogenesis with specific EC and stromal cell combinations. Finally, the unique matrix‐centric perspective of these studies provides strong evidence to justify the preferential selection of MMP‐degradable peptide crosslinkers in synthetic hydrogels used to study vascular morphogenesis and promote vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…However, cells encapsulated within hydrogels can quickly remodel their surroundings by assembling secreted proteins around themselves [4][5][6] . Although it has long been known that cells secrete proteins pericellularly, it is now clear that local cell-mediated modifications can quickly override the physical and biological cues presented by the hydrogel.…”
Section: Ulrich Blache Molly M Stevens and Eileen Gentlemanmentioning
confidence: 99%
“…However, this is now changing. It has been recently shown that, when encapsulated within hydrogels, human bonemarrow-derived MSCs (hMSCs) quickly modify their surroundings by secreting and assembling proteins around themselves [4][5][6] (Fig. 1).…”
Section: Cell-mediated Matrix Remodellingmentioning
confidence: 99%
See 1 more Smart Citation